2007
DOI: 10.1016/j.ab.2006.10.042
|View full text |Cite
|
Sign up to set email alerts
|

Transchip: Single-molecule detection of transcriptional elongation complexes

Abstract: A new single molecule system -Transchip -was developed for analysis of transcription products at their genomic origins. The bacteriophage T7 RNA polymerase and its promoters were used in a model system, and resultant RNAs were imaged and detected at their positions along single template DNA molecules. This system, Transchip, has drawn from critical aspects of Optical Mapping, a single molecule system that enables the construction of high resolution, ordered restriction maps of whole genomes from single DNA mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…An EC may consist a long strand of nascent RNA produced from a single round of transcription [24], while the majority of ECs we observed consist of a "supercomplex" which resulted from multiple rounds of transcription from the same promoter being packed together. The molecular component and structure for "supercomplex" will be discussed in greater detail in later sections of this paper.…”
Section: Transcription Product Detection By Fluorescence Microscopymentioning
confidence: 95%
See 4 more Smart Citations
“…An EC may consist a long strand of nascent RNA produced from a single round of transcription [24], while the majority of ECs we observed consist of a "supercomplex" which resulted from multiple rounds of transcription from the same promoter being packed together. The molecular component and structure for "supercomplex" will be discussed in greater detail in later sections of this paper.…”
Section: Transcription Product Detection By Fluorescence Microscopymentioning
confidence: 95%
“…Our previous results showed that imaged punctates were ECs being paused or arrested at the DNA backbone during the transcription process under certain experimental conditions [24]. An EC may consist a long strand of nascent RNA produced from a single round of transcription [24], while the majority of ECs we observed consist of a "supercomplex" which resulted from multiple rounds of transcription from the same promoter being packed together.…”
Section: Transcription Product Detection By Fluorescence Microscopymentioning
confidence: 96%
See 3 more Smart Citations